(untitled) (Global Journal of Science Frontier Research, 2017)
Recently, Raina and Srivastava and Srivastava and Hussain have provided closed-form expressions for a number of an Eulerian integral involving multivariable H-functions. Motivated by these recent works, we aim at evaluating a general class of multiple Eulerian integrals concerning the product of two multivariable A-functions defined by Gautam et Asgar[4], a class of multivariable polynomials and the extension of the Hurwitz-Lerch Zeta function. These integrals will serve as a fundamental formula from which one can deduce numerous useful integrals.